STRATEGI KOMUNIKASI ANTAR BUDAYA KAUM PERANTAU - Chrisma Juwita, Tina; Purwanti, Angel (LPPM Universitas Putera Batam, 2022)
Paguyuban Kepodang Mas, better known as a community group, that gathers based on the same ethnicity, namely Javanese ethnicity, is a community that was founded on April 25, 2010, based on ideas and agreements from people from Banyumas, Purbalingga, and surrounding areas who live and settle in Batam city. Paguyuban Kepodang Mas has two community goals, the first is to strengthen the ties of brotherhood among Purbalingga residents who live in the same area, in this study is Batam City and the second is to create and maintain unity and unity in-order-to create a more intimate sense of brotherhood. thorough. The purpose of this study was to find out how the intercultural communication strategy in the existence of the identity of the immigrants in Batam City in the Kepodang Mas Community took place. This study uses a descriptive qualitative research method with the technique of observation, in-depth interviews, and documentation. The result of this research is that the communication strategy carried out by the Kepodang Mas Community is considered successful because it gets the attention of the public in carrying out its activities. There are four forms of communication strategies carried out by the Kepodang Mas Community, namely: (1) Indirect communication through social media Facebook, Whatsapp, and Youtube; (2) Interpersonal communication for fellow members through monthly meeting, lottery club, and visitting each member’s home; and (3) Public communication through art performances, annual gathering, and socialization